Disaster Preparedness and Sensitivity Level among Higher Education Institution Students - Lilybeth Musong Matunhay (International Journal of Disaster Management, 2022)
Disaster preparedness is an important factor that plays a major role in diminishing the causalities in case of any disasters. In the Philippines, Davao Region also frequently experiences various disasters due to geological, morphological, and climate characteristics. Earthquakes, flooding, and landslides are the premise fields of these disasters. Furthermore, devastating earthquakes and floods that are seen as a result of global climate change shaved to significant loss of both life and property in the region. It is imperative to increase the knowledge and attitude of people regarding natural and man-made disasters in order to make them able to cope with their adverse effects. In this paper, an attempt has been made to access the knowledge, attitudes, and practices of college students in the region. Results revealed the need to highlight the need for disaster safety education among students. Descriptive statistics are used in the analysis and evaluation of the data. By revealing the level of awareness at the higher education level, the result of the study could be a potential basis for disaster mitigation education intervention that includes relevant topics on disaster preparedness and resiliency. Results revealed that an information source repertoire has to be strengthened and reconsidered to meet information insufficiencies and explore more structural factors to address the gap as it is evident in the result that the students who have taken disaster training are reported to have more positive opinions compared to those who have none.